(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
اتجه الاقتصاد العالمي في القرن الحالي نحو عولمة الإنتاج والأسواق، وقد أثّر هذا الاتجاه على البيئة الإنتاجية وجعلها تتسم بخصائص تختلف عمّا هي عليه بالبيئة التقليدية. وقد أدّى الانتقال إلى بيئة تصنيعية حديثة تعكس وتتجاوب مع المنافسة الخارجية ومتطلبات العملاء إلى وجود بعض نواحي القصور في النظام المعياري للتكاليف، الأمر الذي أأوجب ضرورة تطويره ليلائم بيئة الأعمال الحديثة. يناقش البحث نواحي التطوير اللازمة ليعكس نظام التكاليف المعياري الخصائص المرنة لبيئة الأعمال الحديثة وليخدم الأغراض الإدارية في المشاريع التي تطبقّه. وقد توّصل إلى مجموعة من النتائج أهمها: • لا يقلل تطبيق نظم التصنيع الحديثة من دور نظام التكاليف المعيارية بل يزيد من أهمية هذا الدور ولكن بعد تطويره بما ينسجم مع متغيرات البيئة الحديثة للصناعة. • بيّنت نتائج اختبار فرضيّ البحث، أنّ هناك فروق ذات دلالة معنوية بين خصائص البيئة الإنتاجية التقليدية والحديثة، وإنّ الانتقال إلى بيئة التصنيع الحديثة قد أثر على عدم قدرة النظام المعياري التقليدي على توفير المعلومات التكاليفية اللازمة للإدارة للقيام بوظائفها المختلفة. • يمكن تطوير النظام المعياري على أن يؤخذ بعين الاعتبار مجموعة من الأمور منها: • ملاءمة أسلوب تطوير المعايير لطبيعة المنُتج والمرحلة التي يمر بها خلال دورة حياته. • ربط بناء المعايير بالأنشطة أو عمليات المعالجة الصناعية. • تطوير مدخل التحليل التقليدي للانحرافات وبما يحسن من دور نظام التكاليف المعيارية في دعم نظم الرقابة وتحقيق استراتيجية التحسين المستمر. Global economics directs toward market and production Globalization in the current century. This tendency affects production environment, and distinguishes it by features which are differ from what was in traditional one. This shifting to modern manufacturing environment which reflects and responses with external competition and customer’s needs, make some defects of standard cost system come to light. And this by its turn necessitate improves it to be suitable to modern business environment. This research discusses the needed improvement aspects in projects which apply the standard cost system to make it able to reflect the flexible characteristics of modern business environment and to serve managerial targets . The research reaches to some results, the most important of those are: • Applying the modern manufacturing systems don’t lessen the role of standard cost system, but it increase the importance of it if it is developed to harmonize modern manufacturing environment variables. • Testing research hypothesis emphasize that there is significant difference between the features of traditional and modern environment, and the shifting to modern one makes the standard cost system unable to provide needed cost information to enable management does its various functions. • It’s possible to develop standard cost system by taking some aspects in mind which is: • Fitting adopted technique in improving standards to product nature and its stage in its life cycle. • The standards build must be connect with activities or manufacture dealing processes. Develop traditional analyze approach as a requirement to improve standard cost system’s role in supporting control systems and achieving continuous improving strategy.